Exploring Informal Vocational Training (IVT) and its Missing Accreditation Link with Formal Vocational, Technical and Professional Education and their Implications: A Sociological Study in a City of India - Bazaz, Rabiya Yaseen; Akram, Mohammad (Journal of Education Culture and Society, 2022)
Aim. This empirical study aims to conceptualise the prevalence of Informal Vocational Training (IVT) in India. It also explores the missing link at accreditation level between IVTs and other formal vocational, technical and professional courses and depicts their implications in the occupational, economic, social and cultural lives of people. Methods. This study was conducted in the Srinagar city of the Union Territory of Jammu and Kashmir in India. Both the survey method and the case method were used for collecting the primary data and applying triangulation methodologically. Results. This study reveals that elites generally dominate in the prestigious technical and professional courses because of better accessibility and affordability, and that the vulnerable sections miss many of these opportunities. The vulnerable sections very often get the benefits of IVTs learnt outside the formal system in finding some employment, but such employment attracts lower prestige and income than what they get through formal technical and professional courses. IVTs find no academic recognition in the existing accreditation system, and so people culturally and socially associated with these IVTs continue to remain deprived. Conclusion. There is a need to develop a credit-based link between IVTs and formal vocational, technical and professional courses so that the skills learnt through IVTs could get transferred to the formal system and attract better occupational and economic rewards. The findings are relevant for both developing and developed societies, but more particularly for societies having a considerable presence of informal economy because IVTs exist more within these economies.